Achievement Level of Compulsory and Major English Groups of B.Ed. Students in Subject Verb Agreement of English - Rai, IchchhaPurna (Rupantaran: A Multidisciplinary Journal, 2022)
This paper attempts to test the achievement level of students who are studying English as a Compulsory English (hereafter CE) and a Major English (hereafter ME) at Bachelor of Education (hereafter B.Ed.) level at Dhankuta Multiple Campus under Tribhuvan University's syllabus. Both CE and ME groups are being taught the same books as the Compulsory English in the same class by the same teacher. Most of the CE groups fail in the exam in compulsory English. On the basis of findings, this paper recommends that both CE and ME should not be taught together in the same class. They should be treated differently in different classroom.